Comparative imaging of European eels (Anguilla anguilla) for the evaluation of swimbladder nematode (Anguillicoloides crassus) infestation - Frisch, Kathleen; Davie, Andrew; Schwarz, Tobias; Turnbull, James (Journal of Fish Diseases, 2016)
This study compares diagnostic imaging tools in detecting the parasitic swimbladder nematode Anguillicoloides crassus in Anguilla anguilla (L.) and focuses on ultrasound in an attempt to develop a non-destructive, field diagnostic test. Ultrasound use could allow the parasite to be diagnosed without decreasing the number of critically endangered European eels through post-mortem. In the preliminary study, eels were examined with computed radiography, computed tomography, magnetic resonance imaging, 14MHz high-end ultrasound and 5MHz low-end portable ultrasound, and the results were compared with post-mortem findings. This ultrasound scanning technique did not produce any promising results. A second batch of eels was examined using the same high-end and low-end ultrasounds, but employing a different scanning technique and comparing the results with post-mortem. This second study, scanning along the midline from below, allowed for the detection of anomalies associated with moderately infected animals. None of the eels used in this study were severely infected; thus, no conclusions can be made regarding the use of ultrasound in those animals. Overall, it was found that none of the techniques were useful in diagnosing mildly infected individuals; therefore, no single diagnostic imaging tool is sensitive enough to replace post-mortem for definite diagnosis.